KAJIAN DAYA DUKUNG PONDASI JALAN UNTUK RELOKASI JALAN LINGKAR TOWNSITE PADA PT. BUKIT ASAM (PERSERO), TBK, UNIT PENAMBANGAN TANJUNG ENIM, SUMATERA SELATAN - Rendi Julianto Elsa; Syamsul Bahri; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2018)
PT Bukit Asam (Persero), Tbk as the one of STATE-OWNED company under the Ministry of Energy and Mining was the main manufacture of coal mining industry in Indonesia, located at Tanjung Enim, South Sumatera. There are three sites in PTBA mining permit area, Tambang Air Laya, Muara Tiga Besar, and Banko Barat. On the site of Tambang Air Laya will planned an expansion of the pit area and build a new Lingkar Townsite road for fluency mobilization. There are several problems have been founded to build a roads in Lingkar Townsite road, such as the unknown value of basic soil density and physical properties of soil layers, and also there is a weak point of the road beause there is a former swamp that directly closed without throwing away the mud first such as STA point 200, 300, 400, 600, 700, 800, 900, 1100, 1300, and 1400.To solving those problems is done by testing the density of the soil with the Dynamic Cone Penetrometer (DCP) and the California Bearing Ratio (CBR). And also physical properties testing such as atterberge, paraffin wax density, water content, and grain size is done with. In addition to direct the testing in field, the testing is also done as a light compaction test in labor as an order to guidelines doing compaction for the road. On the compaction for the road there are three stages of compactions work that is basic layers compaction, bottom binders layer, and top binders layer.Based on basic soil hardness test the result values of CBR test are 6.56 %, 3.98 %, 5.29%, 3.96%, 3.86%, 5.63% , 8.90%, 6.74%, 5.48% , 5.73%, 5.61%. The type of soil at Lingkar Townsite relocation road is loam soil and silty soil. Many Compactor track doing soil compaction, for compacting Basecose B is 11 tracks and for Basecose A is 10 tracks. After doing the compation will get the value of final road. After doing the compaction the result values pf CBR are 14.7% , 72.69%, 58.39%, 35.00%, 36.78%, 21.85%, 31.69%, 51.31%, 27.21%, 13.43%.Keywords : Road compaction, Dynamic Cone Penetrometer (DCP), and CaliforniaBearing Ratio (CBR)